"The House with a Garret" - E. Gaškienė-Červinskienė (Literatūra (Vilnius))
In the article the investigator indicates the contradictory interpretation of Tchekhov's work „The House with a Garret" is due to the ignoration by literary criticism of the writer's poetical properties. Attention is paid to typical shortcomings of the analysis of works of art in general. The story is analysed as a monolithic unity, taking into consideration both Tchekhov's artistic system ·and the properties of this particular work, as an artistic phenomenon. The significance of the context and the artistic function of all the elements of the story is emphasized.